Alpha-synuclein dimerization in erythrocytes of patients with genetic and non-genetic forms of Parkinson's Disease. (13th April 2018) - Papagiannakis, Nikolaos; Koros, Christos; Stamelou, Maria; Simitsi, Athina-Maria; Maniati, Matina; Antonelou, Roubina; Papadimitriou, Dimitra; Dermentzaki, Georgia; Moraitou, Marina; Michelakakis, Helen; Stefanis, Leonidas
Highlights: Erythrocyte membrane α-syn dimer is elevated in PD patients with no known mutations. Erythrocyte membrane α-syn dimer is elevated in PD patients with GBA mutations. There is no α-syn dimer level difference in p.A53T α-syn mutation carriers. The increased α-synuclein dimer levels may be due to altered lipid composition of the erythrocyte membrane. Abstract: Background: Variations of α-synuclein levels or species have been reported in Parkinson's Disease (PD). There has been little systematic examination of erythrocytes, a rich source of α-synuclein. Methods: Erythrocyte membranes were obtained from PD patients (mutation carriers in the α-synuclein gene (A53T-PD) and glucocerebrosidase gene (GBA-PD) (n = 18 each), and patients without known mutations (GU-PD, n = 56)), and age-/sex-matched controls (n = 56). Levels of monomeric and dimeric α-synuclein were assessed using Western immunoblotting. Results: A statistically significant increase of α-synuclein dimer and dimer to monomer ratio was found in GBA-PD and GU-PD. In contrast, dimer levels of A53T-PD were not different from controls. No difference was found in α-synuclein monomer levels. Conclusions: The increased α-synuclein dimer in GBA-PD and GU-PD is suggestive of an apparent systemic dysfunction causing the dimerization, and potentially oligomerization, of α-synuclein. These results may have implications for PD pathogenesis and biomarker development.